2021
DOI: 10.1002/acr2.11343
|View full text |Cite
|
Sign up to set email alerts
|

Four Systemic Lupus Erythematosus Subgroups, Defined by Autoantibodies Status, Differ Regarding HLA‐DRB1 Genotype Associations and Immunological and Clinical Manifestations

Abstract: Objective. The heterogeneity of systemic lupus erythematosus (SLE) constitutes clinical and therapeutical challenges. We therefore studied whether unrecognized disease subgroups can be identified by using autoantibody profiling together with HLA-DRB1 alleles and immunological and clinical data.Methods. An unsupervised cluster analysis was performed based on detection of 13 SLE-associated autoantibodies (double-stranded DNA, nucleosomes, ribosomal P, ribonucleoprotein [RNP] 68, RNPA, Smith [Sm], Sm/RNP, Sjögren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
1
32
1
Order By: Relevance
“…However, in contrast to the other study [30], we did not observe any association between anti-Pg antibodies and SLE per se or SLE disease activity. This discrepancy may be related to statistical power, since the other study was larger than ours (n = 303 versus n = 101), or to the type of SLE patients included, as SLE is a notoriously heterogenous disease [46]. We found no association between elevated anti-Rgp IgG levels and presence of autoantibodies in general, including RF, ANA and aPL antibodies, in any of the two cohorts investigated.…”
Section: Discussioncontrasting
confidence: 65%
“…However, in contrast to the other study [30], we did not observe any association between anti-Pg antibodies and SLE per se or SLE disease activity. This discrepancy may be related to statistical power, since the other study was larger than ours (n = 303 versus n = 101), or to the type of SLE patients included, as SLE is a notoriously heterogenous disease [46]. We found no association between elevated anti-Rgp IgG levels and presence of autoantibodies in general, including RF, ANA and aPL antibodies, in any of the two cohorts investigated.…”
Section: Discussioncontrasting
confidence: 65%
“…We show using factor analysis that SLE in our cohort demonstrated 4 clinical and 3 antibody-based subtypes. Recently, Diaz-Gallo et al showed that 4 SLE subgroups based on autoantibody profile could be distinguished (13). Idborg et al showed that there were differences at the proteomic level based on SLE antibody profile (15).…”
Section: Discussionmentioning
confidence: 99%
“…Given the complex heterogeneity of SLE, several studies have attempted to classify the disease into subgroups for purposes of improved clinical management. These subgroups have been based on clinical patterns (13,14), auto-antibody profiling (13)(14)(15), organ domains (16), flares (17,18), remission patterns (19), and treatment response (20). Using unsupervised cluster analysis, Diaz-Gallo et al (13) identified four distinct subgroups based on auto-antibody profiling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ADs share risk factors (e.g., environmental and genetic) and immunological mechanisms (4). A single autoimmune disease may manifest with autoantibodies of diverse organ specificities (i.e., latent polyautoimmunity) (5)(6)(7). Polymorphisms in HLA-DRB1, HLA-DQB1, CD226, PTPN22, STAT4, GPR103, TNFAIP3, and LRP1/STAT6 are associated with multiple ADs (8,9), including systemic and organ-specific ADs (10).…”
Section: Introductionmentioning
confidence: 99%